EFFECT OF HONEY ON HEALTHY AND ALLOXAN DIABETIC MALE SWISS-WEBSTER MICE (MUS MUSCULUS) WITH AND WITHOUT GLIBENCLAMIDE THERAPY - Andy Susbandiyah Ifada; Andreanus Andaja Soemardji; Ilma Nugrahani (School of Pharmacy Institut Teknologi Bandung, 2021)
This study was conducted to know the effect of honey from Sumbawa on healthy and alloxan-induced diabetic mice. It consisted of honey quality test, glucose tolerance test (GTT) and alloxan-induced diabetes. On GTT, healthy animals were given pure honey, diluted honey 20% and 50%, blood glucose levels were measured every 30 minutes for 3 hours. Diabetic mice obtained by inducing alloxan at a dose of 50 mg/kg bw. Blood glucose levels of diabetic mice in range of 400-500 mg/dL. Honey and combination of glibenclamide with honey were given for 21 days. Glibenclamide dose of 0.65 mg/kg bw was used as standard drug. Blood glucose levels were measured on days 10, 17 and 24. On the next day, the animals were sacrificed and pancreas were isolated. Pure honey, 20%, and 50% honey showed to raise blood glucose levels. Blood glucose level in mice group that given pure honey stayed in the normal value of 140 mg/dL until 180 minute observation, significantly different from the group of glucose 20% (p<0.05). Honey and combination of glibenclamide with honey in alloxan diabetic mice did not caused a decrease of blood glucose levels that significantly different compared to the sore group (p>0.05). It can be concluded honey maintains blood glucose levels of healthy mice on a normal value of 140 mg/dL until 180 minutes. In alloxan diabetic test, neither honey nor the combination of glibenclamide and honey did not show a decrease in blood glucose levels that significantly different to the sore group.